Multi-criteria wind energy siting assessment : a case study in the West Fjords - Barajas, Renata Stefanie Bade, 1993- (2019)
Visualizing data through maps may aid in the strategic implementation of wind energy. Strategic implementation refers to holistic, multi-faceted site selection that addresses the common issues associated with wind energy generation. Current siting methods emphasize cost and prediction of power production. This study will expand on the state-of-the-art by addressing the effects of power generation on the transmission system and displaying results in user-friendly visuals. This research identifies locations best suited for wind energy implementation in the West Fjords of Iceland based on eight criteria: diesel use, electricity use, population size, predicted power, icing, maximum potential generation input, expected power losses, and cost. A multi-criteria assessment method is used to systematically determine ideal wind energy locations in the West Fjords. A sensitivity analysis is conducted as to evaluate the impact of the various input variables on the cumulative score used for site selection. The study found that the Southeastern part of the West Fjords is best suited for developing wind energy when all input variables are weighted equally. It is recommended that a holistic study, such as the one presented in this thesis, is first performed to identify a set of high-value regions which may then be the focus of feasibility studies. Sjónræn greining gagna með hjálp kortagrunna er gagnleg við heildræna ákvarðanatöku vegna uppbyggingu vindorkuvera. Heildræn ákvörðunataka byggir á vali á virkjunarstað með tilliti til margvíslegra þátta sem jafnan reynast erfiðir eða umdeildir við slíka uppbyggingu. Oft á tíðum eru ákvarðanir um virkjunarkosti teknar á grunni kostnaðar og orkuvinnslu. Í þessu verkefni er tekið tillit til fleiri þátta, og áhrifa raforkuframleiðslunnar á raforkukerfið, og er leitast við að setja niðurstöður fram á sjónrænan hátt. Verkefnið snýst um að finna hentug svæði til vindorkuframleiðslu á Vestfjörðum að teknu tilliti til átta áhrifaþátta: notkun dísel í raforkuframleiðslu, raforkunotkun, ...